CORRELATION BETWEEN GLYCAEMIC CONDITIONS WITH SIRT-1 GENE EXPRESSION LEVELS IN THE PROGRESSION OF DIABETIC RETINOPATHY - Shaik, Mahaboob Vali; S, Skandha Harshita; Shaik, Munni; shaik, John basha; Molli, Nissi; Kuragayala, Swarna deepak; G, Jayaram; Kola, Vijaya Shekar (Indonesian Vitreoretinal Society, 2025)
Background: Diabetic retinopathy (DR), a microvascular disorder, is commonly linked to diabetes. Diabetes mellitus' complex, progressive, and asymptomatic neurovascular effects make DR the leading cause of blindness and visual impairment in people of working age. Retinal neovascularisation determines whether DR is proliferative, non-proliferative, or diabetic macular oedema. Aim: To evaluate the levels of SIRT-gene mRNA expression and how they relate to glycaemic status in patients with diabetic retinopathy. Methods: The 60 cases in this study included 30 patients with diabetic retinopathy, 30 diabetic cases without retinopathy, and 30 non-diabetic controls. SIRT1 mRNA expression and basic laboratory measures were recorded. Results: It was demonstrated that DR patients have down-regulated SIRT1 mRNA expression. The results of the study suggest that DR results from an imbalance between SIRT1 and IL-17 expression levels, with SIRT1 perhaps offering protection by preventing the production of IL-17. The DR cases had significantly lower levels of SIRT1 gene mRNA expression than the controls. The association between SIRT1 mRNA expression and four putative functional SNPs (rs12778366, rs3758391, rs2273773, and rs4746720) was examined. The findings showed that the allelic genes of rs3758391 showed substantial changes in SIRT1 mRNA expression in the healthy subjects (p<0.01). Compared to the controls (0.91±0.75 fold), SIRT1 mRNA expression levels were lower in the RD (0.61 ± 0.29 fold). SIRT1 gene expression decreases when HbA1c rises, indicating a negative connection between SIRT1 expression and HbA1c. This suggests that SIRT1 plays a protective function in preventing diabetic retinopathy (r = -0.245, p = 0.004). When comparing the Diabetes with Retinopathy Group to the Diabetes without Retinopathy Group1, SIRT1 Gene Expression was considerably lower, but IL17 was significantly greater (0.62±0.30 vs. 0.60±0.27, p=0.012). Conclusion: In conclusion, the present data provide credence to the idea that the rs3758391 SNP affects mRNA expression in healthy people and that the SIRT1 gene guards against DR. In connection with the pathophysiology of DR, they also clarified the processes controlling the genetic regulation of the SIRT1 gene.